Establishment and characterization of a new mouse gastric carcinoma cell line, MCC - Yushen Wang; Xianju Li; Yi Wang; Jun Qin (Cancer Cell International)
Abstract Background The aim of this study was to establish a primary mouse gastric carcinoma cell line. Methods Gastric adenocarcinoma in the body region was induced in immunocompetent BALB/c mice using N-Methyl-N-nitrosourea and a 2% NaCl solution. Fresh gastric cancer tissue samples were cultured in 1640 medium supplemented with 10% fetal bovine serum for primary culture and subculture. Cellular morphology was assessed via light microscopy, and a cell growth curve was established. Genomic and proteomic analyses were conducted to characterize the molecular features of the cell lines. This cell line demonstrated a 100% success rate in forming subcutaneous tumors in BALB/c mice. By integrating proteomic profiles from clinical gastric cancer patients and the murine subcutaneous tumor model, several molecular targets suitable for preclinical investigation were identified. Trametinib, a MEK inhibitor, was employed as a model compound in our preclinical study. Results A novel gastric carcinoma cell line, designated MCC, was established from BALB/c mice. This cell line exhibited a doubling time of approximately 33 h. Genomic and proteomic analyses identified mutations frequently observed in clinical gastric cancer patients, such as Kras, Egfr, and Ccnd3. Additionally, MCC overexpresses proteins, including SLC1A5, MCM6, and ITGA2, which are significantly upregulated in gastric cancer tissues compared to adjacent non-cancerous tissues. The MCC cell line demonstrated stable tumorigenicity in immunocompetent BALB/c mice, forming subcutaneous tumors that closely resemble the proteomic profile of clinical gastric cancer samples. This high concordance facilitated the identification of several potential therapeutic targets for gastric cancer. Preclinical studies with trametinib revealed that treatment effectively inhibited gastric cancer growth, likely mediated through the activation of immune cells, particularly neutrophils and T cells. Conclusions The MCC cell line serves as an indispensable model for gastric cancer research, offering a robust platform for investigating tumor development and progression. Its exceptional tumorigenic capacity and strong concordance with clinical proteomic profiles underscore its significance in translational research, facilitating the discovery of novel therapeutic targets and elucidation of molecular pathways critical for developing effective treatment strategies.